Development of E-Worksheet Using Using Android Educapps Application for Economic Learning - Rizal Rizal; Abdullah Igo; Latief Sahidin; Andi Julia Nurrachman Muhtar (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to develop an e-worksheet on learning and teaching economics using the android educapps application. The method used was research and development through the ADDIE model. The data were collected through questionnaires, interviews, and documents. The implementation of the product trial was carried out at State Senior High School 2 Kendari with 50 students. The data obtained were analyzed qualitatively through the results of assessments from experts, the results of product trials and the use of t-tests on the assessment of the results of electronic worksheets that had been done by students during the large product test.   The results of the product assessment showed that 89.14% of all aspects of the e-worksheet have been feasible, and this percentage was the very good category. The assessment of IT experts showed that aspects of software engineering and aspects of visual communication received a score of 79.94%. The results of the material expert assessment concluded that all aspects of content feasibility, presentation feasibility aspects and language assessment aspects received a score of 91.5%. Based on this assessment, the educapps application was declared eligible as an economics learning e-worksheet for class XI at State Senior High School 2 Kendari. The results of the study have implications for teachers' understanding of the development of e-worksheets and teaching materials that can be harmonized with technological developments so that learning can be in accordance with the needs of today's global education.